A Counter-Forensic Audit Trail: Disassembling the Case of The Hateful Eight. (November 2019) - Fuller, Matthew; Mazurov, Nikita
Forensics is proposed as a means to understand, trace, and recompile data and computational activities. It has a securitocratic dimension and one that is being developed as a means of opening processes, events and systems into a more public state. This article proposes an analysis of forces at play in the circulation of a 'screener' of Quentin Tarantino's The Hateful Eight and associated files, to suggest that forensic approaches used to control flows of data may be repurposed for dissemination. The article maps a brief history of digital forensics and sets out some of its political entailments, indicating further lines of enquiry regarding the inter-relation of technosocial powers constituted in the interactions between forensics and counter-measures. The article proposes that the posthumanities are partially constituted by a renewed relationship between questions of culture, subjectivity, knowledge and the technical. Some propositions for the technical as grounds for cultural politics are made.